2020
DOI: 10.1093/intimm/dxaa032
|View full text |Cite
|
Sign up to set email alerts
|

Increased urinary exosomal SYT17 levels in chronic active antibody-mediated rejection after kidney transplantation via the IL-6 amplifier

Abstract: Chronic active antibody-mediated rejection (CAAMR) is a particular problem in kidney transplantation (KTx), and ~25% of grafts are lost by CAAMR. Further, the pathogenesis remains unclear, and there is no effective cure or marker. We previously found that a hyper NFκB-activating mechanism in non-immune cells, called the IL-6 amplifier, is induced by the co-activation of NFκB and STAT3, and that this activation can develop various chronic inflammatory diseases. Here, we show that synaptotagmin-17 (SYT17) is inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 56 publications
1
27
0
Order By: Relevance
“…For immune-related traits, the significant QTL for CAPA_105 was detected on SSC3 and the Synaptotagmin-17 ( SYT17 ) gene was the candidate gene in the QTL region. SYT17 is increased in the exosomal fraction of urine, and this increase is associated with activation of the IL-6 amplifier in humans 41 . Complement component 3 (C3), which plays a vital role in CAPA, is an acute-phase protein whose expression is regulated by cytokines such as IL-6 42 .…”
Section: Discussionmentioning
confidence: 97%
“…For immune-related traits, the significant QTL for CAPA_105 was detected on SSC3 and the Synaptotagmin-17 ( SYT17 ) gene was the candidate gene in the QTL region. SYT17 is increased in the exosomal fraction of urine, and this increase is associated with activation of the IL-6 amplifier in humans 41 . Complement component 3 (C3), which plays a vital role in CAPA, is an acute-phase protein whose expression is regulated by cytokines such as IL-6 42 .…”
Section: Discussionmentioning
confidence: 97%
“…Synaptotagmin-17 (SYT17) is also specifically and highly expressed in the kidney. After kidney transplantation, the expression level of SYT17 in urinary exosomes was specifically elevated during CAMR compared to that in normal conditions, renal tubulointerstitial lesions, or CsA nephrotoxicity [ 29 ] ( Table 1 ). The general tetraspanin marker CD9 was used to set up a normalization of urine dilution and showed that SYT17/CD9 could diagnose CAMR with a high AUC value of 0.82.…”
Section: Discussionmentioning
confidence: 99%
“…This indicates that CD4+ T cell-derived cytokines such as IL-17A may lead to sustained activation of IL-6 due to T-cell activation and local accumulation that are not related to antigen specificity ( 51 ). To support this, it is shown that synaptotagmin-17, a type of urinary exosome, is increased in association with IL-6 amplifiers in patients with chronic active antibody-mediated rejection in kidney transplantation ( 52 ). These were considered that may be relating the suppression of cytokines by hydrogen and may affect the results of mild fibrosis and tubular atrophy in the H-DCD20 ( 29 , 34 ).…”
Section: Discussionmentioning
confidence: 99%